Environmental Science and Policy - Elena Louder; Carina Wyborn; Christopher Cvitanovic; Angela T. Bednarek (Elsevier, 2025)
Evaluating the impacts of environmental science on policy and practice is inherently challenging. Impacts can take a variety of forms, occur over protracted timeframes and often involve subtle and hard-to-track changes. As a result, diverse impacts are impossible to capture through traditional academic metrics such as publications and citations, and cannot be captured by focusing solely on end results of a given research project, such as changes in policy or practice. However, despite these challenges, environmental scientists are increasingly required to demonstrate the impact of their work, for example, in funding applications or for career progression. As a result, there has been increased effort among academics and practitioners alike to develop frameworks to guide the evaluation of impacts at the intersection of environmental science, policy, and practice. In this paper we syn- thesize this rapidly developing landscape of evaluation frameworks. Drawing from literature across fieldssuch as co-production, knowledge exchange, boundary-spanning and other related subdisciplines, we explore common themes and areas of divergence across the different evaluation frameworks. Through qualitative analysis we show that the differences between frameworks often trace back how knowledge is understood and what counts as impact. We conclude by reflectingon our analysis, and articulating ‘rules of thumb’ to help guide the selection of an evaluation framework. In doing so, we hope that this synthesis contributes towards a growing community of practice aimed at supporting an improved relationship between environmental science, policy and practice.